Adaptability of Performing Literature Speech Tadut Artist in Facing Social Change of Peoples' Life Besemah Pagaralam - Sabillah, Masayu Selly; Triyanto, Triyanto; Utomo, Udi (Universitas Negeri Semarang, 2017)
Tadut speech literature is a literary speech that developed in Besemah Pagaralam which is used as a medium for dissemination and learning of Islam in the recitation and death because his poems are able to remind people of Allah swt.. Problems reviewed ini this research, (1) How to show literature Tadut speech in the community culture of Besemah Pagaralam (2) What values of local wisdom are expressed in Tadut's literature, (3) How does the adaptation of the literary performers of Tadut's literary works defend the language of the Tadut literature his artistry in the social change of life of the people of Besemah Pagaralam. This research uses interdisciplinary approach that is the science of cultural anthropology, sociology and art education. The type of research method used is qualitative with case study design. Data is collected by observation techniques, interviews and document material collection. The results show, first, in the present day Tadut literature is shown in government events, race events, public events and even wedding ceremony. Second, the values of local wisdom expressed in Tadut literature are religious values, moral values, educational values, customs values. Third, adaptability done by Tadut literary artists through the mechanism of cultural collaboration is able to maintain its existence in social change.